Examen especial a la Unidad Administrativa de Talento Humano de la Gobernación de Los Ríos, aplicando la norma 407 de control interno en el año 2014. - Cruz Zambrano, Aída Nicelly (2015)
This research was conducted in the Human Resource Management Unit of the Government of the Province Rivers; it is located on Avenida General Barona and Sucre (corner) in Canton Babahoyo which is the seat of the province.; It is an institution of government public character; whose purpose is to provide service to the public, granting of annual operating permits, residence certificates delivery, ensure implementation of provincial development strategies of the Government. The overall objective was to conduct a special examination of the Human Resource Management Unit of the Government of Rivers, applying the standard 407 Internal Control; for which several types of research used; according to the purpose of research, research method, investigation techniques and the level of research, with the sole purpose of making an accurate analysis of the study variables in the process of fulfilling the duties and responsibilities Human Resource Management Unit, in order to draw conclusions and recommendations. This required interviewing staff of this department (three) and analyze the current regulations to which it is governed; this allowed to conclude that its organizational structure is outdated, knowing that not motivated or employees are trained, that manual job classification is not given to all personnel entering to work has not been done performance evaluation, besides the Administrative Unit of Talent does not have a plan of promotions and advancement, nor does the rotation of staff in established periods and there is an appropriate mechanism to.